In-Service Teacher Professional Development: Challenges and Opportunities for Innovating the Trichronous Modality of Delivery in Vietnam’s EFL Education - Tuyen Van Nguyen; Helena Sit (Education Sciences)
The evolving landscape of educational technology has not only affected the design of teaching learning contents but also the employment of methods of delivery. In Vietnam’s language education discipline, research indicates that the integration of educational technology has significantly expanded the range of delivery modalities available to educators. However, whether the existing modalities can effectively cater to the needs of diverse learning styles remains uncertain. To bridge the research gap, this study initially seeks to assess the effectiveness of commonly utilized delivery modalities in K-12 EFL education. Thirty volunteer EFL teachers from across Vietnam, representing the north, central, and south regions, participated in in-depth interviews. These teachers teach English at primary, secondary, and high schools. The main findings include their current ICT competence levels and preferences for instructional design regarding diverse modalities of delivery. Then, grounding on an in-depth analysis of their choices and perspectives, a trichronous model is proposed and innovated to accommodate diverse learning preferences and maximize learning potential. The research findings and proposal are significant for professional development trainers and teacher educators, providing valuable insights for decision-making regarding the increasing use of technology in current EFL research and practice. This study can contribute to shaping a forward-thinking approach to EFL education in an increasingly digitalized world by addressing challenges and identifying more practical practices in language teacher education.